Student Perceptions on Online Learning for Indonesian General Course In The Pandemic Covid-19 Phase - Ari Suryawati Secio Chaesar; Titi Setiyoningsih (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The Covid-19 pandemic has had an impact on the education sector. The government's efforts to break the chain of the spread of the Covid-19, which is growing massively, is by implementing an online learning policy. This study aims to determine student perceptions of online learning for Indonesian general courses in the Covid-19 pandemic phase. This study uses a survey method approach with a descriptive nature which aims to describe the situation or phenomenon that occurs. The subjects of this study were Sebelas Maret University students who were active in the odd semester of the 2021/2022 academic year, totaling 124 students. Data collection techniques were carried out by distributing questionnaires filled out online by students. The results showed that online learning can be accessed easily (66.1% agree), provide high learning motivation (48.4% agree and 48.4% disagree), online learning does not provide high learning motivation (50.8 % agree), carried out on time according to the study schedule (63.7% agree), learning materials are presented in accordance with the syllabus (71.8% agree), the lecturer responds to questions and opinions that arise (64.5 % agree), the lecturer gives you the opportunity to give questions or opinions (62.9% agree), online learning makes me believe the value of the Indonesian general courses that are followed increases (67.7% agree), the media/application used is very good easy to use (78.2% agree), easy to collect assignments and exams online (69.4% agree). It can be concluded that online learning for Indonesian general courses in the Covid-19 pandemi phase received a good response from students and it is recommended that lecturers always provide motivation to students.